Facing Death, Facing Life - Gavshon, Ingrid (South Africa, 2002)
Portrait of a man who is trying to come to terms with life having faced death. In 1984, Duma Khumalo was sentenced to death by hanging for his alleged participation in the mob killing of a town councilor in Sharpeville, South Africa. The trial was a miscarriage of justice that was not exceptional in apartheid South Africa. Duma Kumalo spent 3 years on death row (7 years in jail) and was given a stay of execution, 15 hours before he was due to be hanged for a murder he did not commit. His experience on death row heightened the sense of injustice that he felt growing up under apartheid in South Africa. Duma’s reprieve ended his waiting, but since, he has been struggling to make meaning of life after near death since "… facing death is hard, but, facing life after facing death, is even harder.”
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films